Banach-Mazur Distance Between Two Dimensional Banach Spaces - Al-Mezel, S. A. (Sarajevo Journal of Mathematics, 2024)
The purpose of the present paper is to investigate geometric properties of two-dimensional Banach spaces. We are also concerned with the Banach-Mazur distance between Banach spaces. For real or complex spaces $d(l^2_1,l^2_p)= 2^{1-\frac{1}{p}},$ if $1≤ p≤ 2$ and if $1≤ p≤ ∞$ and $l_p^2$ is two-dimensional real space, then $d(l^2_1,l^2_p)= 2^{\frac{1}{p}}.$ 1991 Mathematics Subject Classification. 46B03, 46B03